AKTIVITAS HARIAN DAN DETEKSI STRES PADA SAPI PERANAKAN ONGOLE (PO) DAILY ACTIVITIES AND DETECTION OF STREE ON PO CATLE BY MEASUREMENT OF CORTISOL HORMONE LEVELS - Jauhari Efendy (Universitas Madura, 2018)
The study aims to observe behavior and stress levels to PO cattles in group housing of